BUD23 promote the cell proliferation ability by affecting the PPAR signaling pathways: evidence from the online dataset and cell experiment - Tao Huang; Binbin Jiao; Zhenkai Luo; Xiaolei Zhang; Zengjun Wang (Discover Oncology)
Abstract Introduction Prostate cancer is a major public health challenge for men worldwide, being the second most common cancer diagnosis and the fifth leading cause of cancer-related deaths among men. The etiology of prostate cancer is multifactorial, with age, genetic predispositions, and lifestyle factors playing critical roles. The role of the peroxisome proliferator-activated receptors (PPARs) in prostate cancer remains complex and not fully elucidated. Methods Transcriptomic data from The Cancer Genome Atlas (TCGA) were utilized for this study. The data were analyzed using single-sample Gene Set Enrichment Analysis (ssGSEA), Gene Ontology (GO) enrichment analysis, KEGG pathway analysis, and Gene Set Enrichment Analysis (GSEA). A prognosis-prediction model was constructed using Cox regression and LASSO analysis. Functional experiments, including Western blotting, quantitative PCR (qPCR), Cell Counting Kit-8 (CCK-8) assays, and EdU incorporation assays, were performed to validate the role of BUD23 in prostate cancer. Results Significant differences were observed in the immune microenvironment and HLA gene expression profiles between high and low PPAR expression groups in prostate cancer. The high PPAR group exhibited a less active immune microenvironment with higher fractions of immunosuppressive T regulatory cells (Tregs). A robust prognostic model identified key genes, including BUD23, associated with patient survival. Elevated BUD23 expression was correlated with more aggressive clinical features such as advanced pathological stages, nodal metastasis, and higher Gleason scores. Knockdown of BUD23 in PC-3 and LNCaP prostate cancer cell lines significantly inhibited cell proliferation. Western blotting and qPCR confirmed effective BUD23 knockdown, and CCK-8 and EdU assays demonstrated reduced cell proliferation. BUD23 knockdown resulted in significant reductions in PPAR-α, PPAR-β, and PPAR-γ protein levels, suggesting a regulatory axis between BUD23 and PPARs in prostate cancer. Conclusion The study highlights the distinct roles of PPARα, PPARβ/δ, and PPARγ in prostate cancer progression and their potential as therapeutic targets. Elevated BUD23 expression is associated with aggressive prostate cancer features and patient survival, making it a potential prognostic biomarker. The knockdown of BUD23 not only inhibited cell proliferation but also reduced the expression of PPAR-related proteins, indicating a potential regulatory axis between BUD23 and PPARs. These findings suggest that targeting BUD23 could modulate PPAR signaling and inhibit tumor growth in prostate cancer.